MORPHOLOGICAL AND BIOMETRICAL STUDY ON ADULT RAMS, BUCKS, AND BULLS TESTIS IN DUHOK PROVINCE - SOFI, SALEEM ABDULLAH (Journal of Duhok University, 2022)
Fifteen paired testes of apparently healthy adult Local rams, bucks, and bulls were collected from the slaughterhouse in the Duhok province, to compare their gross morphology and biometrical parameters. Each testis position, form, structures, size, and relationship to other elements of the region were recorded. The testes of three species were oval, and the largest was in bull and the smallest in buck. The average weight, length, circumference, volume and density of both testicles in the ram, buck, and bull varied significantly (p≤0.05) from each other. The mean thickness and width of the left and right testicles in the three species didn’t differ significantly. The ram testicular density and volume were significantly different (p≤0.05) in comparing biometrical values between the left and right testes, The length, volume, and density of the left and right testes differed significantly (p≤0.05) in the buck. The circumference, volume, and density of the left and right testes were significantly different (p≤0.05) in bulls, whereas the other values did not statistically different. The tunica albuginea was soft and grayish red in rams and bucks, but was a dense blue-gray membrane in bulls. The parenchyma layer of the testis revealed creamy white in both ram and buck but was yellow to creamy orange in the bull. In conclusion, this study has shown the similarities and differences in terms of gross morphology, morphometry between the testes of ram, buck, and bull